2019
DOI: 10.3390/nu11102369
|View full text |Cite
|
Sign up to set email alerts
|

Association between Food Store Availability and the Incidence of Functional Disability among Community-Dwelling Older Adults: Results from the Japanese Gerontological Evaluation Cohort Study

Abstract: This study sought to clarify the association between food store availability and the incidence of disability in older adults. This study utilized a population-based cohort study of independent Japanese adults aged ≥65 years, which was a 6 year follow-up of participants in the Japan Gerontological Evaluation Study. A total of 31,273 respondents were extracted. Food store availability was evaluated based on the existence of food stores within 500/1000 m of the home. We utilized participant-reported subjective me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Although, for example, random survival forest may have advantages when handling complex and high-dimensional data [37], it has not yet been confirmed whether it is superior to Cox proportional hazards models for all types of health outcomes, such as cancer or cardiovascular disease incidence [33,38,39]. In this study, we selected five neighborhood environmental variables based on previous neighborhood research and applied Cox models for the ease of consistent interpretation of our results with previous studies [34][35][36]40,41]. Considering different features of the residential municipalities, we performed subgroup analysis by each residential municipality.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Although, for example, random survival forest may have advantages when handling complex and high-dimensional data [37], it has not yet been confirmed whether it is superior to Cox proportional hazards models for all types of health outcomes, such as cancer or cardiovascular disease incidence [33,38,39]. In this study, we selected five neighborhood environmental variables based on previous neighborhood research and applied Cox models for the ease of consistent interpretation of our results with previous studies [34][35][36]40,41]. Considering different features of the residential municipalities, we performed subgroup analysis by each residential municipality.…”
Section: Discussionmentioning
confidence: 94%
“…Cox proportional hazards model were conducted to estimate the hazard ratio (HR) with 95% confidence intervals (CIs) for the incidence of becoming physically inactive by each neighborhood environmental factor as a primary exposure variable, i.e., land slope, bus stop density, intersection density, residential density, and distance to community center. Cox proportional hazards models are commonly used in public health research to estimate the effect of several variables from the time until a specific outcome (e.g., physical inactivity, functional disability, mortality) takes place [33][34][35][36]. For each neighborhood environmental factor, the correlation with the other environmental factors was verified, and a high correlation was confirmed (r ≥ 0.4, Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the food-insecure elderly of this study, the risk of malnutrition or frailty was found to increase with increased negative perceptions of local community food store accessibility, which might imply that the local community food environment affected the food or nutrient intake of individuals, even for vulnerable elderly in an urban area. Previous studies have reported that the local community food environment is an important factor for food selection, quality of meals, and health outcomes [ 18 , 19 , 36 ]. In this study, the malnourished or frail elderly had a lower intake of meats, vegetables, and fruits than those who were not, and their corresponding energy, protein, iron, and vitamin intakes were also lower, as a result.…”
Section: Discussionmentioning
confidence: 99%
“…The food environment refers to the physical, economic, political, and socio-cultural environment affecting the food choices and nutritional status of individuals [16]. The local food environment has been emphasized as a factor that could influence the adequacy of food intake, food insecurity, and health status [17][18][19][20]. Previous studies have shown that the factors affecting food insecurity in the elderly are their area of residence, social isolation, low economic level, housing cost, family composition or living alone, oral health status, disability, chronic comorbidity with medication, frequency of food purchase, and difficulty in preparing food [14,15,21,22].…”
Section: Introductionmentioning
confidence: 99%